2014
DOI: 10.3892/etm.2014.1639
|View full text |Cite
|
Sign up to set email alerts
|

Protective mechanism of Xuebijing injection against heat stroke in rats

Abstract: This study aimed to investigate the protective mechanism of Xuebijing injection (XBJ) against heat stroke (HS) in rats. Adult male Sprague Dawley rats were randomly divided into normal control (NC), normal saline-treated HS (NS-HS) and XBJ-treated HS (XBJ-HS) groups. At 47 and 57 min from the initiation of heat stress (42.5–43.5°C), the plasma levels of certain cytokines [interleukin (IL)-1β, IL-6 and tumor necrosis factor-α], biochemical indicators (creatinine, blood urea nitrogen, aspartate aminotransferase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…It is usually induced by heat stress and tends to result in high mortality and deformity (1). To date, the underlying mechanisms of heat stroke have remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually induced by heat stress and tends to result in high mortality and deformity (1). To date, the underlying mechanisms of heat stroke have remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…A present study [9] demonstrated that XBJ acts against heat stroke by decreasing the level of interleukin 1b, interleukin 6, and tumor necrosis factor a. These results suggest that the positive effect of XBJ on random skin survival may be associated with increasing glutathione level and decreasing certain cytokines.…”
Section: Discussionmentioning
confidence: 53%
“…XBJ injection is a traditional Chinese medicine preparation and has been widely used clinically for the treatment of sepsis, and it is beneficial to inhibit inflammatory reaction and oxidative stress in China [12]. The main effective components of XBJ are safflower yellow A, tetramethylpyrazine, paeoniflorin, and ferulic acid [9]. Safflower yellow A is the main active ingredient of Carthamus tinctorius L. Recent studies [14,15] demonstrated that safflower yellow A could attenuate apoptosis, protein oxidation, and I/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations